Approaches to Sumerian literature : studies in honor of Stip (H.L.J. Vanstiphout) - Michalowski, Piotr, 1948-; Veldhuis, Niek; Vanstiphout, H. L. J. (Herman L. J.) (Cuneiform monographs, 2006)
This volume, dedicated to H.L.J. Vanstiphout at the occasion of his retirement from the University of Groningen, July 14th 2006, demonstrates the broad variety of scholarly approaches to the study of ancient Sumerian literature. It contains contributions by Bendt Alster ("Ninurta and the Turtle"), Nicole Brisch ("In Praise of the Kings of Larsa"), A.J. Ferrara ("A Hodgepodge of Snippets"), Alhena Gadotti ("Gilgames, Gudam and the Singer"), W.W. Hallo ("A Sumerian Apocryphon?"), Dina Katz ("Appeals to Utu"), Jacob Klein ("Man and His God"), Piotr Michalowski ("The Strange History of Tumal"), Gonzalo Rubio ("Sulgi and the Death of Sumerian"), Niek Veldhuis ("How Did They Learn Cuneiform?"), and Claus Wilcke ("Die Hymne auf das Heiligtum Kes").